Autonomous and remotely operated service operation vessels in wind farms: A study exploring the practical utilization of autonomous and remotely operated service operation vessels during dynamic positioning operations in offshore wind farms. - Degrell, Fredrika (My University, 2023)
In response to the societal pressures for developing green energy sources to address the wicked problems of climate change, the maritime sector has witnessed a rapid development of offshore wind farms, particularly in Northern Europe. Part of the operational strategy to improve the opportunities for exploiting wind-based energy harvesting, are investments in digitalization and increasing levels of autonomous technologies. To maintain a safe and reliable operation and environmental protection it is critical that these technologies can be managed by human operators. This thesis examines the practical deployment of automation-based technology during dynamic positioning operations within wind farms according to dynamic positioning operators. An ethnographic study was conducted to map goal-based tasks during dynamic positioning operations within a wind farm. Dynamic positioning operators were requested to reflect on the practical possibilities of deploying automation-based technology to improve or substitute DP tasks during semi-structured interviews. One researcher and three developers within autonomous and remote steering were also interviewed using a semi-structured approach to obtain their take on human-machine interaction issues. A thematic analysis of the interviews detected the main attributes of tasks that could be allocated to autonomy or remote handling respectively. These findings were compared to previous research and deliberated in the discussion section. When human life is at risk, the response time is limited, and the outcome uncertain a task was considered high-risk. Primarily, these are tasks conducted close to installations and tasks relating to emergency response. There are several methods and aids to improve human-machine interaction issues, enhancing the use of autonomous and remote operations within wind farms. Nevertheless, the specific capabilities of humans in what is defined as high-risk situations should not be undervalued. Therefore, high-risk tasks are only practically deployed to any other party than a human under the circumstance that there is a human on board the vessel, monitoring with sufficient situation awareness and competence to take control when needed.
Keywords: Maritime autonomous surface ships; autonomy; remote operations; shore control center; dynamic positioning; offshore wind farm; human-machine interaction